2016
DOI: 10.1371/journal.pone.0158382
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about Childhood Vaccination in the United States: Political Ideology, False Consensus, and the Illusion of Uniqueness

Abstract: Several contagious diseases were nearly eradicated through childhood vaccination, but some parents have decided in recent years not to fully vaccinate their children, raising new public health concerns. The question of whether and how beliefs about vaccination are linked to political ideology has been hotly debated. This study investigates the effects of ideology on perceptions of harms and benefits related to vaccination as well as judgments of others’ attitudes. A total of 367 U.S. adults (131 men, 236 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 47 publications
10
67
2
1
Order By: Relevance
“…However, liberal (left-wing) respondents differentiate a great deal between their personal opinion and their perception of others' opinions. These results corroborate previous findings in the literature on false consensus (e.g., Amit et al, 2010;Dvir-Gvirsman, 2015) and false uniqueness (e.g., Rabinowitz et al, 2016;Stern et al, 2014). Furthermore, the comparison between opinions toward same-sex female parenting and working mothers might also indicate that…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, liberal (left-wing) respondents differentiate a great deal between their personal opinion and their perception of others' opinions. These results corroborate previous findings in the literature on false consensus (e.g., Amit et al, 2010;Dvir-Gvirsman, 2015) and false uniqueness (e.g., Rabinowitz et al, 2016;Stern et al, 2014). Furthermore, the comparison between opinions toward same-sex female parenting and working mothers might also indicate that…”
Section: Discussionsupporting
confidence: 90%
“…In a study of Israeli voters, extreme left-wing supporters had a tendency for false uniqueness, which might be explained by their motivation to be perceived as a unique minority and distinct from conventional right-wing voters (Babad & Yacobos, 1993). Moreover, liberals tended to underestimate their similarity with other people due to their desire to feel unique (Rabinowitz, Latella, Stern, & Jost, 2016;Stern, West, & Schmitt, 2014).…”
Section: N T E R N a T I O N A L J O U R N A L O F P U B L I C O P mentioning
confidence: 98%
“…On several issues, my collaborators and I find that conservatives exhibit a “truly false consensus effect”—assuming that like–minded others share their opinions more than they actually do, whereas liberals exhibit an “illusion of uniqueness”—assuming that like–minded others share their opinions less than they actually do (Rabinowitz, Latella, Stern, & Jost, ; Stern, West, & Schmitt, ). Thus, we see an especially stark asymmetry when it comes to relational motivation (see also Stern & West, ).…”
Section: Ideological Asymmetries In Relational Motivationmentioning
confidence: 99%
“…More interestingly, perhaps, Rabinowitz et al () observed that liberals underestimated the extent to which others shared their own (relatively favorable) beliefs about childhood vaccination; they assumed that the attitudes of the general public, other liberals, and conservatives were more divergent from their own attitudes than was actually the case (see Figure ). Moderates, too, underestimated how similar their own attitudes were to those of the general population and to those of liberals, but they did not distort the differences between their own attitudes and those of conservatives.…”
Section: Ideological Asymmetries In Relational Motivationmentioning
confidence: 99%
See 1 more Smart Citation